Resin Infiltration in the Treatment of Enamel Hypoplasia: Case Report - Arantes, Fernanda Novais; Gontijo, Sávio Morato de Lacerda; Barreiros, Ivan Doche; Ferreira, Juvenil Alves Neves Diniz; Novaes Júnior, João Batista; Silami, Francisca Daniele Jardilino (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Objective: this case report aims to describe the clinical the treatment of enamel hypoplasia in tooth 11, in a 23-year-old female patient, through the resinous infiltrating. Case report: briefly, the hypoplasic lesion was treated with 15% hydrochloric acid for 2 minutes. Then 99% alcohol was applied over the lesion for 30 seconds and resin infiltration for 3 minutes, followed by light curing for 40 seconds. Again, infiltrating resin was applied for 1 minute and light cured. After that, finishing and polishing were carried out with finishing cup and polishing discs, followed by a felt and paste disk. Conclusion: it can be concluded that the protocol used in this case report proved effective and produced excellent esthetic results.